Multicultural Education at Pesantren (The Study of API ASRI Islamic Boarding School at Tegalrejo Magelang) - Siyono, Siyono (CV. Creative Tugu Pena, 2021)
The article aimed to determine the multicultural education in the API ASRI Tegalrejo Magelang Islamic boarding school. This research is a field research that uses a qualitative approach. The subjects of this research were the caregivers of the pesantren, the head of the pesantren, the board of the pesantren, the ustadzah and students. The data in this study were obtained through observation, interviews, and documentation. The results of this study resulted in several findings: Multicultural education at API ASRI Tegalrejo Magelang Islamic boarding school has been implemented since the establishment of the pesantren. This is based on the educational curriculum used in the API ASRI Tegalrejo Magelang Islamic boarding school which uses three curriculum systems: a. Kemendikbud curriculum, b. Pesantren curriculum / those made by pesantren, c. Hidden Curriculum / unplanned curriculum. Multicultural education in the education system is not just a need for students but for all Muslims, because Islamic teachings contain multicultural teachings, so its implementation is more due to an effort to practice Islamic teachings. Multicultural education at API ASRI Tegalrejo Magelang Islamic boarding school, has not been optimal. This is evident that the students understand more about multiculturalism between religious communities rather than understanding the internal multiculturalism of religions, even though understanding the internal multiculturalism of religion should be prioritized, because students will live more together with the same religion than with different religions, so that the internal multiculturalism of the religious community is more important. found rather than multicultural between religious communities. Keywords: Multicultural Education, Multiculturalism of Religion, Educational Pesantren